RECRUITMENT AND SELECTION STRATEGIES OF PUBLIC SECTOR UNDERTAKINGS - U, Sajeena (International Journal of Research -GRANTHAALAYAH, 2017)
This study examines the impact of recruitment and selection strategies of public sector undertaking .In the Indian context, Public sector or the PSEs primarily constitute the corporate bodies where 51% or more equity is held by the government, created under the special acts of legislature, or registered under the companies Act 1956.Primary data on various aspects of recruitment and selection were collected from the employees of different undertakings with the help of well framed questionnaire that was duly filled by the HRM officials and employees. This study highlight the emerging trends in the recruitment and selection strategies of public sector undertaking and the major obstacles that are being faced by the companies.